Renal disease due to snake-bite and its management - Sheriff, M.H.R. (My University, 1983)
Renal failure remains a serious late complication of snake-bite envenomation and contributes significantly to mortality. Clinical effects depend on the degree of envenomatior type of snake and speed of antivenom administration amongst other factors. The renal effects range from none at all to proteinuria, mild oliguria, haemoglobinuria, haematuria and severe olio guric renal failure. Immediate hospitalisation, early and effective antivenom administration and meticulous attention to fluid and electrolyte balance are essential measures. Consumption of king-coconut water has been found to make management difficult. Mannitol challenge and maintaining hydration have helped to avoid peritoneal dialysis and therefore its hazards. Dialysis therapy when indicated, careful post dialysis care, aided by renal biopsy when recovery is slow are measures that are recommended. The role of intravenous heparin needs further clinical study. In bilateral and diffuse cortical necrosis no renal recovery is possible and the only mode of therapy would be regular dialysis treatment and kidney transplantation.